SOCIAL WORK ROLES AND THE WELLBEING OF ORPHANS AND VULNERABLE CHILDREN IN CALABAR MUNICIPALITY, CROSS RIVER STATE, NIGERIA - NNANA OKOI OFEM; RITA NGOZI OKAFOR; LILIAN OTU UBI (International Studies Journal)
The main focus of this study was on Social Work Roles and the Wellbeing of Orphans and Vulnerable Children in Calabar Municipality, Cross River State, Nigeria. To achieve this, three specific objectives were formulated to guide the study thus: to examine the condition and challenges of orphans and vulnerable children (OVC) and their wellbeing in Calabar Metropolis; to identify the roles of the government and non-governmental organization towards the wellbeing of orphans and vulnerable children in Calabar metropolis, and to examine the roles of social workers toward the vulnerable and orphan children and their wellbeing in Calabar Metropolis. These specific objectives were further used to formulate research questions and hypothesis for the study. Relevant literatures were reviewed based on the subject under discussion. The study was further supported by two theories: Human Capital theory and John Bowly's Attachment theory. The study employed the cross-sectional research design, the population of the study comprised of 371,022 as the main population of the study area. The sample size for the study was 150 respondents randomly selected from the total population of the study area. The questionnaire was the main instrument for data collection. The research utilized the primary and secondary sources of data collection. From the analysis of findings, the following recommendation was made amongst others: Social worker should help using social work skills in the enumeration of the effects associated to orphan and vulnerable children.